2023
DOI: 10.1371/journal.pone.0282790
|View full text |Cite
|
Sign up to set email alerts
|

Does deep neuromuscular blockade provide improved perioperative outcomes in adult patients? A systematic review and meta-analysis of randomized controlled trials

Abstract: Deep neuromuscular blockade provides better surgical workspace conditions in laparoscopic surgery, but it is still not clear whether it improves perioperative outcomes, not to mention its role in other types of surgeries. We performed this systematic review and meta-analysis of randomized controlled trials to investigate whether deep neuromuscular blockade versus other more superficial levels of neuromuscular blockade provides improved perioperative outcomes in adult patients in all types of surgeries. Medline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Meanwhile, low IAP may negatively affect the operation conditions. Studies have shown that deep muscle relaxation can improve the surgical conditions of endoscopic surgery 16,17 . However, it remains unclear whether neuromuscular block (NMB) can reduce the IAP and improves the cognitive function of patients under the operating conditions required by surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, low IAP may negatively affect the operation conditions. Studies have shown that deep muscle relaxation can improve the surgical conditions of endoscopic surgery 16,17 . However, it remains unclear whether neuromuscular block (NMB) can reduce the IAP and improves the cognitive function of patients under the operating conditions required by surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…While we are requesting additional analyses from the authors, the benefits of DNMB on postsurgical pain are nonetheless evident, and have been well established previously in the context of laparoscopic surgeries [ 6 , 7 ]. However, unlike most prior investigations of DNMB versus MNMB on postsurgical outcomes [ 8 ], the article by Tang, et al assesses outcomes that have a significant bearing on patients’ long-term quality of life, including CPSP incidence, daily opioid consumption, and quality of recovery. We congratulate the authors for their specific attention to these too-often-neglected outcomes.…”
mentioning
confidence: 99%